Co-crystal synthesis of 2- and 4-mercaptopyridines with thiourea and its analogue, trithiocyanuric acid. Issue 29 (7th July 2022) - Wzgarda-Raj, Kinga; Książkiewicz, Olga; Palusiak, Marcin
Abstract : For the first time mercaptopyridine co-crystals are reported as a result of the cross-crystallization of two mercaptopyridines with thiourea and trithiocyanuric acid. In one case, the co-crystal was needed to be obtained under dark room conditions. Abstract : This article describes the synthesis of four new co-crystals obtained via cross-crystallisation of 2- and 4-mercaptopyridines with thiourea and trithiocyanuric acid and examines their crystal structures. The resulting structures are the first four reported co-crystals of mercaptopyridines. In one case, the synthesis resulted in the production of a ternary co-crystal of unexpected composition instead of the desired product and the correct co-crystal needed to be obtained under dark room conditions; interestingly, when separated from solution, all four co-crystal samples were fully light resistant. The crystal state of the four co-crystals is stabilized by several N–H⋯S type hydrogen bonds. Additionally, in the case of thiourea co-crystals, additional short contacts of S⋯S type are also observed. This relatively complicated network of intermolecular interactions is fully characterized herein.